Science, technology and cultural heritage proceedings of the second International Congress on Science and Technology for the Conservation of Cultural Heritage, Sevilla, Spain, 24-27 June 2014 - Rogerio-Candelera, Miguel Ángel (CRC Press, Taylor & Francis Group, 2014)
The Second International Congress on Science and Technology for the Conservation of Cultural Heritage was held in Seville, Spain, June 24-27, 2014, under the umbrella of the TechnoHeritage network. TechnoHeritage is an initiative funded by the Spanish Ministry of Economy and Competitivity dedicated to the creation of a network which integrates CSIC and University groups, private companies and end users such as foundations, museums or institutions. The network's purpose is to foster the creation of transdisciplinary (and not only multidisciplinary) initiatives focused on the study of all assets, movable or immovable, that make up Cultural Heritage.